Transmissible Venereal Tumor in a Border Collie Bitch with MDR1 Mutation - Successful Treatment with Lomustine - Cariola Viana, Paula; Castro de Oliveira, André Lucas; Ferreira, Arthur; Santos Guiotti, Izabelle; Bertelis Merlini, Natalie; Zanata Lizardo, Isabella; de Paula Oliveira Salve, Luisa; Fernanda Firmo, Bruna (Acta Scientiae Veterinariae, 2025)
Background: The multidrug resistance (MDR1) gene is responsible for encoding P-glycoprotein (P-gp), a transmembrane efflux pump of intracellular xenobiotics that regulates the distribution, absorption, and elimination of substances in the body. If a mutation occurs, the protein becomes non-functional or partially functional, resulting in higher bioavailability and lower hepatic, renal and intestinal elimination of drugs transported by this route, increasing the risk of toxicity. This report concerns a case of transmissible venereal tumor (TVT) in a Border Collie bitch, with a mutated MDR1 gene, who received an alternate treatment with lomustine. Case: A 2-year-old intact Border Collie bitch, weighing 19.8 kg, whit history of vaccination, deworming, parasite control treatments up-to-date, progestogen use and access to the streets, was treated at the Veterinary Hospital of the State University of Northern Paraná (HV-UENP), Bandeirantes, PR, Brazil. The main complaint was a reddish wound present in the vaginal region for 2 weeks, with active bleeding and abnormal odor. On physical examination, a "cauliflower" lesion was observed in the vulva, with bleeding upon manipulation and foul odor. Through palpation of the vaginal canal, the presence of a rough and firm lesion, friable upon touch was established, with characteristics similar to the vulvar lesion. The suspicion of TVT was confirmed by cytological examination via vaginal canal swab, fine needle aspiration (Fna) and vulvar imprint. Due to the patient's race, testing for the MDR1 mutation was requested and returned positive for the MDR1 gene mutation (homozygosity); for this reason, the use of 3 sessions of lomustine [Citostal®️ at a dose of 70 mg/m2, orally every 21 days] was prescribed, since animals carrying this mutation are sensitive to conventional TVT treatments. The patient showed complete remission, confirmed by negative vaginal cytology after the 3rd session of the established chemotherapy treatment. Discussion: TVT is a highly prevalent clinical condition, characterized by the development of highly vascularized masses of friable consistency affecting mucosal regions, especially the genitals of dogs. TVT transmission happens when viable tumor cells implant themselves onto the mucosa surface or injured membranes. This process can occur through intercourse, biting, or licking the affected area, facilitating the spread between healthy and contaminated individuals. The MDR1 gene mutation, characterized by the deletion of 4 base pairs, can be found in several dog breeds, with a higher prevalence in the collie lineage and grazing breeds. Given this genetic predisposition, testing for the MDR1 gene mutation was indicated for the patient in order to provide a safer treatment, since the 1st-choice antineoplastic drug, vincristine sulfate, is absorbed and excreted by P-gp. The homozygous mutation of the MDR1 gene indicated the need to modify the conventional treatment, opting for lomustine or, alternatively, reducing the usual doses of vincristine sulfate. It is important to note that other medications for TVT treatment, such as doxorubicin and vinblastine, should be prescribed cautiously, as animals may be sensitive to these medications. It is possible to conclude that: an individualized approach in the treatment of the canine border collie patient, diagnosed with TVT and carrying the homozygous mutation of the MDR1 gene was effective, with the use of 3 sessions of lomustine resulting in complete remission confirmed through cytological examination, after the last session. Keywords: TVT, ABCB1-1 Δ, homozygosity, lomustine, P-glycoprotein, chemotherapy, neoplasia.